Genome-wide association studies of oil, protein and fatty acid contents in soybean accessions evaluated in the savannas of Nigeria - Shaibu, A.S.; Yakubu, A.B.; Mohammed, S.G.; Ibrahim, H.; Mohammed, I.B.; Omoigui, L.O. (2025)
Soybean [Glycine max (L.) Merr.] is a globally crucial source of protein and oil for diverse applications. However, genetic studies of these beneficial traits have not been fully exploited in Africa. This study was conducted to determine the quality trait contents of soybean and determine important genetic loci associated with these traits. The average protein content of the soybean was 31.82% and ranges from 14.70 to 46.06%. The mean oil content was 10.34% and ranges from 3.39 to 21.06%. High variability was also observed for the fatty acids among the soybean accessions. Oleic acid had the highest content among all the fatty acids. Genotyping yielded 19,505 SNPs for the 281 soybean accessions. After the first stage filtering, which excluded unmapped markers, 18,270 SNP markers were obtained. The second stage filtering returned 7244 SNP markers. The PIC ranged from 0.1 to 0.5 for the SNP markers. The marker-trait association (MTA) revealed significant genetic loci for some of the quality traits measured. Three loci were identified for with about 7% of the phenotypic variance explained (PVE). For protein, seven loci were identified with five having positive allelic effects. For palmitic, stearic, oleic and linoleic acids, 4, 12, 6 and 9 loci were identified respectively. This study provides information on some important genetic loci for the improvement of quality traits in soybean.